The Unexpected Universe - Eiseley Loren (Harcourt, Brace & World, Inc, 1969)
The Ghost Continent, The Unexpected Universe, The Hidden Teacher, The Star Thrower, The Angry Winter, The Golden Alphabet, The Invisible Island, The Inner Galaxy, The Innocent Fox, The Last Neanderthal, Bibliography.
The Ghost Continent, The Unexpected Universe, The Hidden Teacher, The Star Thrower, The Angry Winter, The Golden Alphabet, The Invisible Island, The Inner Galaxy, The Innocent Fox, The Last Neanderthal, Bibliography.